Studi Kopresipitasi Zn2+ Menggunakan Al(OH)3 sebagai Kopresipitan - Yollafebrisa Wizul; Indang Dewata; Edi Nasra (Departemen Kimia FMIPA UNP, 2013)
Research of study copresipitation Zn2+ using Al(OH)3 as coprecipitant has been done. This study aims to determine the optimum conditions for coprecipitation of Zn2+ by Al(OH)3, and influence of foreign ions. This study uses variation pH about 5,0 – 10,0; variation of eluent volume about 8,0 – 14,0; variation of concentrated HNO3 volume about 1,0 – 5,0; and variation of concentration Cu2+ about 0,8; 1,2; 1,6; 2,0 and 2,4. Measurement concentration of Zn2+ using Atomic Absorption Spectroscopy (AAS) with wavelength of 213,9 nm. The result showed the optimum conditions occur at pH about 8, 12 mL of eluent and 1 mL of concentrated HNO3 with the absorption capacity of 0,074 mg/g. Meanwhile, the presence of foreign ions such as Cu2+ has influenced the coprecipitated Zn where concentration of the coprecipitated Zn decreased with increasing the concentration of foreign ions.